Analisis Kinerja Operasional Bus Trans Metro Deli Rute Tembung – Lapangan Merdeka - Ritonga, Devi Afridayani; Suranto, Suranto; Nasution, Mahliza (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2025)
This study aims to review the performance parameters and user satisfaction of the implementation of Trans Metro Deli buses, especially the Tembung – Merdeka Field route. This research began by observing and collecting data in the field such as the number of passengers, intermediate time, and travel time and distributing a questionnaire to 100 respondents to find out the perception of passengers and passenger satisfaction with the performance of Trans Metro bus services. The methods used in this study are the Importance Performance Analysis and Customer Satisfaction Index methods. Based on the results of the performance parameter review research, an average load factor of 40.57% was obtained, the average travel time was 56.63 minutes, and the intermediate time was 8.99 minutes. So, the load factor parameters and travel time need to be improved because the values are not in accordance with the standards that have been set. Based on the results of the research from passengers' perception of the performance of Trans Mebidang bus services, what needs to be improved are indicators 11, 21 and 22. And based on the results, the level of passenger satisfaction was obtained by 87.036%, including in the category of very satisfied.